RESEARCHES OF PERIAPICAL TISSUES CONDITION DEPENDING ON THE TYPE OF USED METAL CONSTRUCTIONS WITH RESTORATION OR WITHOUT RESTORATION OF CROWN PART BY ARTIFICIAL CROWNS - А.Yu. Kordiiak; N.M. Dydyk; R.R. Pavlychko (Український стоматологічний альманах)
The ultimate mission of root canal obturation is to avoid penetration of oral fluids containing bacteria, to periapical tissues. The purpose of research is far from clinical observations reveal whether there are periapical changes in dependence on the type of coronal restoration of the teeth that were either not covered by artificial crowns. 96 intra-oral X-rays and 50 panoramic X-ray images and records of medical cards of patients (Form .043) primary dental patients (30 women and 20 men) who applied for the purpose of prosthetic treatment, carried out an analysis of 344 teeth, 291of which were endodontycally treated and have medical indications for crowns covering and 53teeth were covered with crowns with preserved pulp. Teeth were divided into eight groups by type of restoration and divided by gender. Term follow-up after endodontic treatment ranged from 4 to 7 years. The calculation of ratios is in the analyzed groups. Shares in the groups were compared using Student's t-test. The result of the study found that from 112 endodontic treated teeth not covered with crowns only 14 teeth are applied pinning system while the teeth covered with crowns from 232 in 107 pins were used for reinforcing construction. Preference for rebuilding tooth with flexible pin provided only 2.68% and 3.88% of cases, that respectively indicates the lack of prevalence of modern methods as the method of choice.